Konstruksi Kalimat Aktif Dan Pasif Dalam Bahasa Karo - Kirani, Sasi; Ernanda, Ernanda; Amri, Ulil (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2025)
The purpose of this work is to describe how active and passive sentence constructions are built in the Karo language, with a focus on syntactic construction patterns. This research is important because the morphological and syntactic systems of the Karo language differ from other regional languages in Indonesia, requiring in-depth research to add new data to regional language linguistic research and regional language preservation. This study uses a qualitative descriptive method. Data were collected from three native speakers of Karo aged between 20 and 50 years old who live in Berastagi subdistrict, North Sumatra, to provide research data in the form of active Karo sentences and passive Karo sentences. The data collection techniques used in this study were interviews, recordings, and transcriptions using the ELAN application. The research analysis model used was the Miles & Huberman (1984) model, which includes data reduction, data presentation, and conclusion formulation. Source triangulation was used for data validity. The findings of the analysis on the construction of active sentences in the Karo language show that the agent is the subject, the verb is the predicate, and the patient is the object. Active sentences have verbs with the prefixes n- and m-. There are syntactic patterns such as SVO (Subject-Verb-Object), VSO (Verb-Subject-Object), and VOS (Verb-Object-Subject) in the formation of active sentences in the Karo language. Then, passive sentence constructions have the patient as the subject, the verb as the predicate, and the prepositional phrase as an optional object. In passive sentences in the Karo language, there are SVPP (Subject-Verb-Prepositional Phrase) and VPPS (Verb-Prepositional Phrase-Subject) patterns. Passive sentences are distinguished by the prefix i- and the infix i-...-i. The results of this study will contribute to the preservation of the Karo language as part of Indonesia's linguistic and cultural diversity and enhance research on regional linguistics.